The Correlation Between Familiarity with Biak Folklore and English Reading Comprehension Competence Among Senior High School Students in Biak Papua - Putri Anugraheli Ramba Orun; Iin Sulastri Ode Ami; Miftahul Jannah (CV. Pusdikra Mitra Jaya, 2026)
This study is based on the issue that English reading materials used in schools are often not connected to students’ local cultural backgrounds, making it difficult for learners to relate texts to their prior knowledge and daily experiences. In Biak, Papua, folklore remains an important cultural resource that is familiar to students and has the potential to support English reading comprehension through cultural familiarity and schema activation. This study aims to identify students’ familiarity with Biak folklore, assess their English reading comprehension competence, and examine the correlation between these two variables. This research employed a quantitative approach with a correlational design. The participants consisted of 120 senior high school students in Biak, Papua. The instruments were a Biak folklore familiarity questionnaire and an English reading comprehension test adapted to the local cultural context. The data were analyzed using descriptive statistics and correlation analysis. The findings show that students had a fairly high familiarity with Biak folklore, with a mean score of 43.38, and a high English reading comprehension competence, with a mean score of 43.25. The correlation analysis revealed a positive and significant relationship between familiarity with Biak folklore and English reading comprehension competence, with a Pearson correlation coefficient of 0.518. It can be concluded that students who are more familiar with Biak folklore tend to have better English reading comprehension. This study implies that local folklore can be integrated into English reading materials to create contextual and culturally responsive learning.